Ancient hybridization and strong adaptation to viruses across African vervet monkey populations - Svardal, Hannes; Jasinska, Anna J; Apetrei, Cristian; Coppola, Giovanni; Huang, Yu; Schmitt, Christopher A; Jacquelin, Beatrice; Ramensky, Vasily; Müller-Trutwin, Michaela; Antonio, Martin; Weinstock, George; Grobler, J Paul; et al. (Nature genetics, 2017)
Analysis of whole-genome sequencing data from 163 vervet monkeys from Africa and the Caribbean shows high diversity among taxa and identifies signatures of selection. Selection signals affect viral processes, and genes that show response to SIV in vervets but not macaques have elevated selection scores. Vervet monkeys are among the most widely distributed nonhuman primates, show considerable phenotypic diversity, and have long been an important biomedical model for a variety of human diseases and in vaccine research. Using whole-genome sequencing data from 163 vervets sampled from across Africa and the Caribbean, we find high diversity within and between taxa and clear evidence that taxonomic divergence was reticulate rather than following a simple branching pattern. A scan for diversifying selection across taxa identifies strong and highly polygenic selection signals affecting viral processes. Furthermore, selection scores are elevated in genes whose human orthologs interact with HIV and in genes that show a response to experimental simian immunodeficiency virus (SIV) infection in vervet monkeys but not in rhesus macaques, suggesting that part of the signal reflects taxon-specific adaptation to SIV.